Austria : Financial System Stability Assessment; Update. (IMF Staff Country Reports; Country Report, 2008)
The Austrian authorities have been making great efforts since 2003 to enhance the quality of banking supervision and keep up-to-date with banking sector developments. Banks face a reputation risk arising from exposure to money laundering/financing of terrorism risk in both domestic and international activities. The authorities have already elaborated contingency plans for dealing with bank failures and other problem cases. Experience elsewhere suggests also that it can be valuable to set up a system that mandates a decision on required remedial action promptly after warning signs are detected.